Analysis of volatile compounds as quality indicators for Fuji apples after cold storage. Issue 6 (4th August 2017) - Lee, Jangho; Jang, Hae Won; Jeong, Moon Cheol; Yoo, SeungRan; Ha, Jaeho
Abstract: Changes in the volatile components in Fuji apples were investigated by the analysis of intact apples using headspace solid‐phase microextraction–gas chromatography–mass spectrometry to assess their quality during long‐term storage at 4°C (3, 6, and 9 months). Three alcohols and 28 esters were identified, and the feeding of precursor alcohols (e.g., butanol, hexanol, and 2‐methylbutanol) resulted in significantly increased amounts of eight esters. Among these esters, the peak area ratios (PARs) of butyl acetate, butyl butanoate, butyl 2‐methylbutanotate, or 2‐methylbutyl acetate to the eight esters were highly correlated with those of their precursor alcohols to the total alcohol content ( R 2  ≥ .9253). In addition, the PAR of precursor alcohols to the total alcohol content, as well as the PAR of these esters to the eight esters, significantly increased during storage at 4°C ( p  < .01). Therefore, it is concluded that PARs can be used as quality indicators for Fuji apples. Practical applications: Quality assessment is crucial in the food industry to maintain food quality. An accurate, rapid method must be available for an assessment of quality. In addition, the identification of reliable biomarkers is imperative for quality assessment. Because of their versatility, volatile compounds in foods can provide considerable information about the quality of foods. In this study, volatile compounds in Fuji apples served as good quality indicators, and these apples were nondestructively analyzed without sample treatment. In addition, multiple volatile indicators were identified and validated. The results suggested that the volatile compounds analyzed by this nondestructive method can serve as indicators for the rapid, robust assessment of the quality of Fuji apples in the agricultural industry.